Territorial scope of Peronist public policy in the province of Mendoza (Argentina), 1946-1955 - Hirschegger, Ivana (Universidad del Pacífico, 2010)
One of the main goals of the social welfare program promoted by Peronism was that the scope of the educational and sanitary service covered a largeportion of the territory, was expanded, and reached remote locations «left behind» in the country. Based on a focused empirical survey carried out in a hardly socio-economically developed department, as was Lavalle, located in the north of the Province of Mendoza, it is investigated whether these social services were actually expanded, and the consequent effects on the educational and sanitary level of the population.